دراسة أولية حول تطور الأكاروس الأحمر ذو البقعتين Koch (Tetranychidae, Acari ) Tetranychus urticae على البندورة والخيار ضمن المختبر وداخل الزراعة المحمية. - صقر إبراهيم; حورية عادل; غالية سهير (Latakia University Journal -Biological Sciences Series, 2018)
أجريت تجارب مخبرية وداخل الزراعة المحمية بهدف دراسة مراحل تطور الأكاروس الأحمر ذي البقعتين وتقدير خصوبة الإناث على كل من العائلين البندورة والخيار. استخدمت طريقة الأقراص الورقية لتنفيذ التجارب ضمن المختبر والورقة الكاملة مع حلقة الفازلين داخل الزراعة المحمية. أظهرت النتائج تفضيل الأكاروس الأحمر ذي البقعتين لعائل الخيار على البندورة في جميع التجارب المنفذة, وقد تفوق العائل كنبات كامل على الأقراص الورقية بالنسبة لعملية تطور الأكاروس وبلوغه, وكانت سرعة وتيرة النمو للأفراد داخل الزراعة المحمية أكبر مقارنة مع ظروف المختبر, إضافة إلى ارتفاع معدل خصوبة الإناث ضمن ظروف الزراعة المحمية بالقياس مع المختبر. An experiment was conducted in laboratory and green house conditions. The objective of this work is to study the average of the Tetranychus urticae Koch development and assess the female fecundity on both hosts plant of cucumber and tomato. The leaf disk method was used to perform the tests within the laboratory and hale leaf with vaziline ring inside the protect agriculture. The result indicated that the T. urticae showed a higher preference to the cucumber than tomato plant in all tests performed. On the other hand, a compression between the same plant the data showed that the complete one showed a higher level of development and short time from (E) to (A) than leaf disk. The growth process for individuals was more rapid in green house than in laboratory condition. This is in addition to higher female fecundity level inside the green house condition if it measured with the laboratory condition.